Pemanfaatan Limbah Minyak Jelantah sebagai Sabun Cuci Padat untuk Pemberdayaan Ibu-Ibu PKK Desa Karangwuni Kecamatan Weru Kabupaten Sukoharjo - Alifia Hidyus, Sofi; Ghinari, Naflianda; Putri Sherlian, Adysta; Aji Gustaman, Fulian; Margono, Sri (Jurnal Bina Desa, 2024)
Cooking oil, particularly palm oil, is an essential part of the cooking process; however, its repeated use results in *minyak jelantah* (used cooking oil), which poses risks to both health and the environment. *Minyak jelantah* contains harmful compounds such as free fatty acids and acrolein, which can cause various diseases and environmental pollution. Field observations indicate that *minyak jelantah* waste is one of the main issues in household waste, primarily due to its high volume and the lack of proper management, which has the potential to contaminate the environment and negatively impact health. In response to this issue, the UNNES GIAT 9 Team in Karangwuni Village, Weru Subdistrict, Sukoharjo Regency, designed a program for the socialization and training of converting *minyak jelantah* waste into solid detergent soap, with the primary target being the PKK women's group. This program aims to raise awareness about the dangers of *minyak jelantah* and provide practical skills in processing it. The program was conducted on August 10, 2024, with 20 participants who took part in the socialization, soap-making practice, and question-and-answer sessions. The results showed that participants actively engaged in the socialization and practice sessions and were able to apply this knowledge sustainably, which is expected to be expanded to a wider community and integrated with other environmental programs. The participants successfully produced solid detergent soap from *minyak jelantah*. The soap-making process included the stages of material preparation, oil purification, NaOH dissolution, mixture blending, solidification, and a neutralization period before the soap could be used. This program not only provides an environmentally friendly waste management solution but also opens economic opportunities through products with marketable value.